A New Species of Hisonotus (Siluriformes, Loricariidae) of the Upper Río Uruguay Basin - Aquino, Adriana E. (2001)
A new species of the hypoptopomatine genus Hisonotus (Loricariidae) is described from a small tributary of the upper rı´o Uruguay basin near the border between Uruguay and Brazil. The new species can be distinguished from all other congeners by the following combination of characters: (1) presence of serrae along distal two thirds of posterior margin of pectoral-fin spine (versus serrae absent, posterior margin smooth); (2) odontodes along anterior margin of snout biserially arranged, dorsad and ventrad series separated by narrow odontode-free area covered by pad of soft tissue; (3) caudal peduncle short (27–34% SL, versus . 34% SL) and deep (13–15 % SL, versus , 13% SL); (4) eye large (15–19% HL, versus , 13% HL); and (5) caudal-fin pigmentation, when well defined, dark brown with a pair of whitish blotches on upper and lower lobes. The significance of the distribution of the new species is discussed relative to the degree of endemism of other fish groups in the Uruguay basin.